1994
DOI: 10.1159/000201136
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Serum Bile Acids in Patients with Colorectal Adenomas during a One-Year Follow-Up

Abstract: We were recently able to show that patients with colorectal adenomas have an increased serum level of the secondary bile acid deoxycholic acid [Bayerdörffer et al.: Gastroenterology 1993;104:145-151]. The course of individual serum bile acids was followed for 1 year in a random subgroup of these patients. The individual serum bile acids of 39 patients, 10 men with adenoma, 12 men without adenoma, 8 women with adenoma, and 9 women without adenoma, were determined at 6-month intervals by gas liquid chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although the secondary acid compounds may promote the growth of colonic adenomas from which adenocarcinomas may eventually arise (106), epidemiological studies of humans have been conflicting. Some case-control studies have found increased levels of fecal or serum bile acids in patients with colorectal adenomas or cancer (21,22,119,201), whereas others have not (105,170,171). The studies have varied significantly in methodology, choice of controls, the type of bile acid measured (primary, unconjugated, secondary, deoxycholate, etc.…”
Section: Toxic Bacterial Metabolitesmentioning
confidence: 99%
“…Although the secondary acid compounds may promote the growth of colonic adenomas from which adenocarcinomas may eventually arise (106), epidemiological studies of humans have been conflicting. Some case-control studies have found increased levels of fecal or serum bile acids in patients with colorectal adenomas or cancer (21,22,119,201), whereas others have not (105,170,171). The studies have varied significantly in methodology, choice of controls, the type of bile acid measured (primary, unconjugated, secondary, deoxycholate, etc.…”
Section: Toxic Bacterial Metabolitesmentioning
confidence: 99%
“…30,31 We found that fecal levels of this bile acid were higher in cases with adenoma than FOB-positive but not FOB-negative controls, although the difference was statistically significant only in the comparison with FOB-positive subjects. In the logistic regression analysis there was an inverse relationship with the ratio for cancer.…”
Section: Discussionmentioning
confidence: 71%
“…Associations between fecal bile acid concentrations and colon cancer are complex given that factors such as gut transit time and pH may also influence fecal SBA concentrations, and it has been suggested that fecal bile acid concentrations may overestimate the amount of DCA in the bile acid pool given that nearly all bile acids that escape EHC are converted to SBA before excretion [104]. Nonetheless, serum DCA levels, which may reflect the bile acid pool more accurately, also have been shown to be higher in patients with colon cancer than in healthy individuals [18, 19]. A potential mechanism for associations between DCA and colon cancer is that DCA may change the balance between apoptosis, proliferation, and differentiation in the intestinal epithelium [64], acting through interference of tumor suppression and enhancing stimulation of growth via cell signaling pathways.…”
Section: Indirect Effects Of the Gut Microbiome In Cancer Developmementioning
confidence: 99%